Regulasi Memori dalam Pengarsipan Rekonstruksi Sejarah - Widiawati, Harfiyah (Wacana, Journal of the Humanities of Indonesia, 2002)
Writing and documentation involve a process of selection and arrangement. Archives; therefore, is a system which organize the documentation of writings, documents and notes. Archives become a structure that organize the documentation of writings, documents and notes. Archives become a structure that organizes memories because of their close ties with the past. Archives legitimize and control the history of mankind. This article seeks to discuss how archive system can reconstruct or construct history of a nation and the relationship between power and archive system. Supersemar is a concrete example or how power constructs a political history regulated for New Order rezime's interests.